Iodine-Mediated Diastereoselective Cyclopropanation of Arylidene Malononotriles by 2,6-Dimethylquinoline - Yavari, Issa; Hosseinpour, Reza; Skoulika, Stavroula (Synlett, 2015)
A novel iodine-mediated reaction of 2,6-dimethylquinoline with Knoevenagel condensation products of malononitrile with benzaldehydes, leading to a facile, one-pot synthesis of 2-aryl-3-(6-methylquinolin-2-yl)cyclopropane-1,1-dicarbonitriles, in moderate to good yields, is described.
Keywords: diastereoselective reactions; cyclopropanation; small rings; iodine; N-heterocycles